Complementation by BCL2 and C-HA-RAS oncogenes in malignant transformation of rat embryo fibroblasts. - Reed, J C (1990)
The BCL2 (B cell lymphoma/leukemia-2) and C-HA-RAS oncogenes encode membrane-associated proteins of 26 and 21 kilodaltons, respectively. Although RAS proteins have long been known for their ability to bind and hydrolyze GTP, recent investigations suggest that BCL2 encodes a novel GTP-binding protein (S. Haldar, C. Beatty, Y. Tsujimoto, and C. M. Croce, Nature [London] 342:195-198, 1989). Cotransfection of BCL2 and HA-RAS oncogenes resulted in morphological transformation of early-passage rodent fibroblasts, rendering these cells tumorigenic in animals and enabling them to grow in semisolid medium. In contrast, cotransfection of BCL2 with oncogenes that encode nuclear proteins (E1A and C-MYC) did not produce malignant transformation, whereas HA-RAS did complement with these genes. These findings suggest that proteins encoded by oncogenes such as BCL2 and HA-RAS, although having similar subcellular locations and perhaps similar biochemical properties, can regulate distinct complementary pathways involved in cellular transformation.